Representatividade quilombola e universidade: a inclusão em questão - Silva, Marília Eduardo (2021)
This work was constituted from the concerns about the black population, more precisely from the discussions about the opportunity for quilombolas to access the university. Therefore, the objective of this study is to demonstrate the insertion of quilombolas until higher education, based on the specificity of their historical context. In this sense, the trajectories of quilombolas, born in Quilombo Nossa Senhora do Rosário, in the city of Três Pontas-MG, is the basis of this work. The approach to the development of this work was done through a case study. The observations on formation and the concept of quilombo complement the surveys on these historical subjects and their specificities. We realized that, even with Public Policies and Access Laws, there are still gaps with the issues of education in our country, requiring more studies, reflections and more careful actions. The black population has historically been affected by the lack of balance of treatment, and quilombolas represent a forgotten and neglected group. Discussions, reflections on quilombola representativeness in universities are fundamental to provide these subjects with real inclusion in society and in a universal way. The challenges, successes and failures of public education policies lead us to know what the reality of quilombolas would be like, that, of the few studies found on the subject, the index of representativeness of these subjects in these spaces is still very timid. The theoretical concepts that support the research come from a set of authors that deal with the theme: History of quilombos in Minas Gerais, Black Territoriality and Black Citizenship in Brazil, Ethnic-racial relations.